(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and the best of prayers and peace be upon our master Muhammad, the faithful prophet of mercy, and upon his pure and virtuous family, and his brightened companions, may Allah be pleased with all of them all, and those who follow them in goodness until the Day of Judgment. As for after.... Talking about the lexical industry and the construction of the hadith text is one of the most important tasks and stresses the duties of those who want to revive the Arabic drawings after they are studied and to show their features and beauties after their obliteration. However, the considered introduction to any lexical treatment and editing must be preceded by making an effort to rescue the texts and verbal contexts from the clutches of idleness and forgetfulness, and the claws of correction, distortion and alteration as possible, because the realization of attention and ideas in analyzing texts and comparing each other does not work; If the confidence in those texts is non-existent, as if the editor or researcher did not verify the correctness of the words and their proof from their users in the way he reached; Because the meanings are shades of words, and it was said in the past: When does the shadow straighten and the stick is crooked .